Pengendalian Minuman Beralkohol Dalam Mencegah Meningkatnya Tindak Pidana Kriminal Di Wilayah Polres Way Kanan - Sari, Sindi Novita; Furqon, Ahmad Fauzi; Edi, Relit Nur (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
Implementation of Article 13 of Way Kanan Regency Regional Regulation Number 3 of 2016 concerning Control of Alcoholic Drinks, with a focus on controlling alcoholic drinks in preventing an increase in criminal acts in the Way Kanan Resort Police area. Alcoholic drinks have been proven to be one of the main triggering factors in acts of violence, as well as other law violations, which have an impact on the crime rate in an area. In this research, a qualitative approach was carried out using interview methods with police officers and the surrounding community. The research results show that although there have been control efforts through regulatory policies and routine operations, there are still challenges in suppressing excessive alcohol consumption, especially among teenagers. The main contributing factors include a lack of public awareness about the negative impacts of alcohol and a lack of strict law enforcement against related offences. Therefore, a more effective control strategy is needed involving various parties, including educational institutions, community organizations, and the police, to increase public understanding and create a safer and more orderly environment. It is hoped that this research can provide recommendations for the authorities in formulating more targeted policies to tackle criminal acts related to alcohol consumption in the Way Kanan Police area